Algures entre o corpo e a representação - Marisa, Cláudia (2017)
This paper reflects over the possibility of a body on stage becoming a dramaturgic language that is capable, through the (re)creation of reality, of attributing sense and meaning to the individual and interpersonal trajectories of performers and the audience, in a dialectic between life and its representations. The main reason for that reflection is found in studies about scenic arts, which state the non-existence of single process to analyse a performance; however, several methods exist that express diverse creation and reception models, in a participating and interactive relation through which interpreters and spectators build their identity around a common "scenic body".